Pendugaan Umur Simpan Keripik Pisang Kapas (Musa Comiculata) dengan Metode Accelerated Shelf-Life Testing (ASLT) Model Arrhenius - Rahmdanti, Alifa Putri; Zainuri, Zainuri; Utama, Qabul Dinanta (Jurnal Teknologi dan Mutu Pangan, 2025)
Shelf life is one of the main problems that is often found in micro and small enterprises (MSEs) that produce banana chips. As a product that has the potential to be marketed widely, it is necessary to estimate the shelf life of the product to fulfill the obligation to include expiry date on the packaging. Therefore, this study aims to determine the estimated shelf life of kapas banana chips. The method used to determine the shelf life of kapas banana chips in this research was Accelerated Shelf-Life Testing (ASLT) with the Arrhenius model. The experimental design in this research is a Completely Randomized Design (CRD) with factorial experiments. The banana chips that will be used as research samples are kapas banana chips that are fried and packaged using aluminum foil packaging and then stored at 3 different temperatures, namely 30o C, 40o C, and 50o C. Sample characteristic were observed on days 0, 5, 10, 15, and 20. The samples are then analyzed for chemical properties, physical properties, and sensory properties. Based on data on the rate of increase in FFA levels, the estimated shelf life of banana chips stored at temperatures of 30o C, 40o C, and 50o C is 93.53 days, 78.37 days, and 66.41 days, respectively. If banana chips are stored at room temperature (28o C), their shelf life is longer, namely 97 days. This study contributes to providing information on the shelf life of banana chip products in terms of maintaining food safety for consumers.